INTEGRATION OF GRAMMATICAL COMPETENCE AND COMMUNICATIVE COMPETENCE ON THE BASIS OF THE COMMUNICATIVE APPROACH - Tursunov Humoyun (International Scientific and Current Research Conferences, 2026)
This thesis explores the integration of grammatical competence and communicative competence within the communicative approach in language education. The study is relevant because grammar teaching in higher education is often separated from real communication, which makes it difficult for learners to use grammatical knowledge in authentic speech. The aim is to identify the theoretical and pedagogical foundations of this integration and to clarify the role of the communicative approach. The research is based on theoretical analysis, comparison, and synthesis of linguistic, pedagogical, and methodological sources. The findings show that effective language use requires both grammatical accuracy and communicative appropriateness. The study concludes that this integration is most effective when grammar is taught through meaningful contexts, communicative tasks, and real speech activity.